Model Validation and Uncertainty Quantification, Volume 3 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Atamturktur, Sez.; Schoenherr, Tyler; Moaveni, Babak; Papadimitriou, Costas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Model Validation and Uncertainty Quantifi cation, Volume 3. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the third volume of ten from the Conference brings together contributions to this important area of research and engineering. Th e collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: • Uncertainty Quantifi cation & Model Validation • Uncertainty Propagation in Structural Dynamics • Bayesian & Markov Chain Monte Carlo Methods • Practical Applications of MVUQ • Advances in MVUQ & Model Updating • Robustness in Design & Validation • Verifi cation & Validation Methods.
1 Bayesian Treatment of Spatially-Varying Parameter Estimation Problems via Canonical BUS -- 2 Bayesian System Identification of Offshore Platforms -- 3 Bayesian Inference and RJMCMC in Structural Dynamics - on Experimental Data -- 4 Approximate Bayesian Computation by Subset Simulation for Parameter Inference of Dynamical Models -- 5 Determining Model Form Uncertainty of Reduced Order Models -- 6 Uncertainty Analysis of Mechanical Behavior of Functionally Graded Carbon Nanotube Composite Materials -- 7 Interval Uncertainty Analysis of Structure Using CANDECOMP/PARAFAC Decomposition -- 8 Uncertainty Quantification For Nonlinear Reduced-Order Elasto-Dynamics Computational Models -- 9 Estimating Noise Spectra for Data from an Instrumented Building -- 10 Uncertainties in an Application of Operational Modal Analysis -- 11 Stochastic Finite Element Model Updating by Bootstrapping -- 12 Dynamic Identification of Classically Damped Uncertain Structures -- 13 Interval Finite Element Approach for Modal Analysis of Linear Elastic Structures Under Uncertainty -- 14 Model Based Effects Screening of Stringed Instruments -- 15 Innovation Dilemmas, Design Optimization, and Info-Gaps -- 16 Approach to Evaluate and to Compare Basic Structural Design Concepts of Landing Gears in Early Stage of Development Under Uncertainty -- 14 Model Based Effects Screening of Stringed Instruments -- 15 Innovation Dilemmas, Design Optimization, and Info-Gaps -- 16 Approach to Evaluate and to Compare Basic Structural Design Concepts of Landing Gears in Early Stage of Development Under Uncertainty -- 17 Robust Sensor and Exciter Design for Linear Structures -- 18 Robust Model Calibration Using Determinist and Stochastic Performance Metrics -- 19 Designing a Mechanical Latch for Robust Performance -- 19 From Model Calibration and Validation to Reliable Extrapolations -- 20 From Model Calibration and Validation to Reliable Extrapolations -- 21 Application of PCA-SVD Validation Metric to Develop Calibrated and Validated Structural Dynamic Models -- 22 An Enhanced Metropolis-Hastings Algorithm Based on Gaussian Processes -- 23 The Challenge of Dynamic Similarity Assessment -- 24 Model Based Robust Balancing Approach for Rotating Machines -- 25 Statistical Modeling of Wavelet-Transform-Based Features in Structural Health Monitoring -- 26 A Bayesian Framework for Optimal Experimental Design in Structural Dynamics -- Towards the Diagnosis and Simulation of Discrepancies in Dynamical Models -- 28 Effects of Prediction Error Bias on Model Calibration and Response Prediction of a 10-Story Building -- 29 Finite Element Model Updating Techniques of Complex Assemblies with Linear and Nonlinear Components -- 30 Metamodeling of Model Evidence -- 31 Calibration, Validation and Cross-Validation of Nominally Identical Car Subframes -- 32 Modeling and Experimental Test Study of a Multilayer Piezoelectric Actuator -- 33 Study of Correlation Criteria for Spacecraft-Launch Vehicle Coupled Loads Analysis -- 34 Full-field Strain Prediction Applied to an Offshore Wind Turbine -- 35 A State-Input Estimation Approach for Force Identification on an Automotive Suspension Component -- 36 A Pretest Planning Method for Model Calibration for Nonlinear Systems.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Solids; Civil engineering; Multibody Systems and Mechanical Vibrations; Solid Mechanics; Civil Engineering